Measurement force, speed, and postmortem time affect the ratio of CNS gray-to-white-matter elasticity - Becker, Julia Monika; Winkel, Alexander Kevin; Kreysing, Eva; Franze, Kristian (Biophysical Journal, 2025)
For several decades, many attempts have been made to characterize the mechanical properties of gray and white matter, which constitute the two main compartments of the central nervous system, with various methods and contradictory results. In particular, the ratio of gray-to-white-matter elasticity is sometimes larger than 1 and sometimes smaller; the reason for this apparent discrepancy is currently unknown. Here, we exploited atomic force microscopy-based indentation measurements to systematically investigate how the measurement force, measurement speed, postmortem interval, and temperature affect the measured elasticity of spinal cord tissue and, in particular, the ratio of gray-to-white-matter elasticity (Kg/Kw). Within the explored parameter space, increasing measurement force and speed increased the measured elasticity of both gray and white matter. However, Kg/Kw declined from values as high as ∼5 at low forces and speeds to ∼1 for high forces and speeds. Kg/Kw also strongly depended on the anatomical plane in which the measurements were conducted and was considerably higher in transverse sections compared with longitudinal sections. Furthermore, the postmortem interval impacted both the absolute measured tissue elasticity and Kg/Kw. Gray matter elasticity started decreasing ∼3 h postmortem until reaching a plateau after ∼6 h. In contrast, white matter elasticity started declining from the beginning of the measurements until ∼6 h postmortem, when it also leveled off. As a result, Kg/Kw increased until ∼6 h postmortem before stabilizing. Between 20 and 38°C, both gray and white matter elasticity decreased at a similar rate without affecting Kg/Kw. We have thus identified differences in the response of gray and white matter to varying strains and strain rates, and the postmortem interval, and excluded temperature as a factor affecting Kg/Kw. These differential responses likely contribute to the contradictory results obtained with different methods working in different strain regimes.
CRIS-Team Scopus Importer:2025-04-18